The effect of wood ash on the soil properties and nutrition and growth of Eucalyptus grandis x urophylla grown on a sandy coastal soil in Zululand - Scheepers, Gerhardus Petrus (2015)
Thesis (MScFor)--Stellenbosch University, 2014.